Competitiveness and marketing strategies of foreign companies in Eastern Europe: Empirical evidence from Finnish and Austrian companies - Jorma Larimo; Jarmo Nieminen; Reiner Springer (Journal for East European Management Studies, 2002)
Research on marketing in Central and Eastern Europe (CEE) has been of rising interest since the transition started in 1989. In this paper two major areas relevant for marketing in CEE are being discussed: the competitive situation in the transition countries and the basic competitive marketing tools for penetrating these markets. This study reports findings of a survey inclu-ding 139 Finnish and 97 Austrian companies active in CEE and confirms: Competition in CEE is intensifying but still weaker than in Western markets. The main competitors are other foreign companies. Western companies base their marketing strategies mainly on personal relationships, technical quality of their product, good company image, personal selling, and customer service. – – Forschungen über das Marketing in Mittel- und Osteuropa (MOE) haben seit Beginn der Transformation 1989 zugenommen. In diesem Artikel werden zwei Bereiche, die für das Marketing in MOE relevant sind, diskutiert: die Wettbewerbssituation in den Transformationsländern und wettbewerbs-orientierte Marketinginstrumente zur Durchdringung dieser Märkte. Die Studie basiert auf einer Befragung von 139 finnischen und 97 österreichischen Unternehmen mit Aktivitäten in MOE und zeigt: Hauptkonkurrenten der befragten Unter-nehmen sind andere ausländische Unternehmen, der Wettbewerb ver-schärft sich ist aber noch schwächer als in westlichen Märkten. Westliche Unternehmen gründen ihre Marketingstrategien hauptsächlich auf gute persönliche Beziehungen, technische Qualität ihrer Produkte, Unternehmens-image, persönlichen Verkauf und Kundenservice.
Keywords: 650